Storytelling for impact: the creation of a storytelling program for patient partners in research - Getchell, Leah E.; Reich, Marian; Allu, Selina; Woods, Cathy; Atkinson, Teresa; Beaucage, Mary; Stalker, Leanne; Sparkes, Dwight; Turner, Catherine; L’Esperance, Audrey; Burns, Kevin; Elliott, Meghan J.; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Storytelling is a powerful means to evoke empathy and understanding among people. When patient partners, which include patients, family members, caregivers and organ donors, share their stories with health professionals, this can prompt listeners to reflect on their practice and consider new ways of driving change in the healthcare system. However, a growing number of patient partners are asked to ‘share their story’ within health care and research settings without adequate support to do so. This may ultimately widen, rather than close, the gap between healthcare practitioners and people affected by chronic disease in this new era of patient and public involvement in research. To better support patient partners with storytelling in the context of a patient-oriented research network, Canadians Seeking Solutions and Innovations to Overcome Chronic Kidney Disease (Can-SOLVE CKD) Network adapted an existing in-person storytelling workshop for patient educators within a hospital setting. The result is a 6-week virtual program called Storytelling for Impact, which guides patients, family members, caregivers and organ donors in developing impactful stories and sharing them at health care and research events, e.g., conferences. The online series of synchronous workshops is co-facilitated by story coaches, who are program alumni and Can-SOLVE CKD staff with trained storytelling experience. Each story follows a structure that includes a call to action, which aims to positively impact the priority-setting and delivery of care and research in Canada. The program has been a transformational process for many who have completed it, and numerous other health organizations have expressed interest in sharing this tool with their own patient partners. As result, we have also created an asynchronous online program that can be used by other interested parties outside our network. Patient partners who share their stories can be powerful mediators for inspiring changes in the health care and research landscape, with adequate structured support. We describe two novel programs to support patient partners in impactful storytelling, which are applicable across all health research disciplines. Additional resources are required for sustainability and scale up of training, by having alumni train future storytellers.

Plain English summary Storytelling is a powerful means to evoke empathy and understanding among people. When patient partners share their stories with health professionals, this can prompt listeners to reflect on their practice and consider new ways of improving the healthcare system. However, as a growing number of patient partners are asked to ‘share their story’ within health care and research settings, there is often not enough tools and resources to support them in preparing their stories in a way that will be impactful for the audience members. Our kidney research network sought to create a novel in-person storytelling program to address this gap within our health research context. The result is a 6-week program called Storytelling for Impact, which guides patient partners—which includes patients, family members, caregivers and organ donors—in developing impactful stories and sharing them in a formal setting. The program is led by story coaches, who are patient partners and staff with trained storytelling experience. Participants are encouraged to include a call to action in their story, which aims to outline clear ways in which health professionals can facilitate positive change in health research or care. Many participants have described the program as transformational, and numerous other health organizations have expressed interest in sharing this tool with their own patient partners. As a result, we have also created a second online program that can be used by other interested parties outside our network. This paper highlights the adaptation process, content, participant feedback and next steps for the program.